2019
DOI: 10.5430/sass.v6n2p46
|View full text |Cite
|
Sign up to set email alerts
|

Responsible Innovation: Moving Towards a Culturally Sensitive Approach

Abstract: Responsible Innovation (RI) recently emerged as an approach that addresses issues related to major social andenvironmental risks and uncertainties in complex innovations. At this stage, more inquiry is still needed to make theWestern-rooted RI approach more contextual and to facilitate its applicability in practice, especially in other culturalsettings. To address this issue, we propose a conceptual framework based on Hofstede’s dimensions of nationalculture and core processes of RI. We argue that the cultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Scholars, analyzing how corporate development rates differ in different societies and entrepreneurial ecosystems, claim that these changes arise because different cultures embrace different principles about the attractiveness and feasibility of a new firm engaged in sustainability activities and a committed CE (Turró et al, 2014 ; Valliere, 2019 ). Likewise, the literature has revealed that the national cultural beliefs of individualism and power distance clarify national variances in the amount of inventiveness (Setiawan et al, 2019 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Scholars, analyzing how corporate development rates differ in different societies and entrepreneurial ecosystems, claim that these changes arise because different cultures embrace different principles about the attractiveness and feasibility of a new firm engaged in sustainability activities and a committed CE (Turró et al, 2014 ; Valliere, 2019 ). Likewise, the literature has revealed that the national cultural beliefs of individualism and power distance clarify national variances in the amount of inventiveness (Setiawan et al, 2019 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…(Birch, 2014) Meanwhile, other studies also show that the use of solar power and green electricity initiatives seems to appeal to consumers with various lifestyles. The attribute of innovation, according to Setiawan and Singh (2019), would hasten the adoption of PV. Various research and studies showed that, in addition to government incentive policies, consumer adoption of PV is influenced by human characteristics like environmental concern, an ecofriendly lifestyle, and consumer innovativeness.…”
Section: Introductionmentioning
confidence: 99%